ANALISIS JURIDIKAL KURANGNYA PERLINDUNGAN NARAPIDANA PENYANDANG DISABILITAS BERDASARKAN UNDANG-UNDANG NOMOR 8 TAHUN 2016 - Muhammad Hidayat; Mitro Subroto (RIO LAW JURNAL, 2021)
This study aims to provide a real understanding of basic governance in order to prioritize guarantees for the fulfillment of idealistic protection, especially for prisoners with disabilities in correctional institutions. The results of this research study will provide answers to problems or obstacles related to the absence of regulations regarding the provision of protection guarantees for prisoners with disabilities which are reviewed based on Law Number 12 of 1995 concerning Corrections. This arrangement expressly only contains in general Law Number 8 of 2016 concerning Persons with Disabilities, thus requiring the complexity of existing regulations by issuing or reviewing normative laws by providing protection guarantees for prisoners with disabilities in the form of Government Regulations concerning the implementation of punishment for persons with disabilities. prisoners. persons with disabilities. And the authors found that there are facilities and infrastructure caused by the number of prisoners who exceed capacity or overcriminalization in correctional institutions, resulting in the implementation of correctional activities that are less than optimal, especially for prisoners with disabilities during the covid-19 pandemic.